Description of the morphology, morphometric, and molecular of Aphelenchoides fragariae (Aphelenchida: Aphelenchoididae) causing crimp disease of strawberry in Indonesia - Kurniawati, Fitrianingrum; Hidayat, Sri Hendrastuti; Tondok, Efi Toding; Syafutra, Heriyanto; Supramana, Supramana (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2025)
Aphelenchoides fragariae, commonly known as strawberry crimp nematodes, primarily target the aerial parts of plants, affecting both internal and external structures. In Indonesia, where strawberries are predominantly cultivated in highland regions, the presence of strawberry crimp disease has been confirmed. Infected plants exhibit symptoms such as stunted growth, reddened foliage, crimped or curled leaves, and malformed buds and blooms. Aboveground damage caused by the nematodes includes contorted shoots, undersized leaves, and reddish petioles, often accompanied by discolored patches on the foliage. These symptoms significantly impair the growth and productivity of strawberry plants, highlighting the nematode’s potential as a serious pest in these regions. The identification of A. fragariae was achieved through a combination of morphological and molecular characterization methods. Species confirmation relied on PCR amplification of the nematode’s cytochrome oxidase subunit I (COI) gene, using primers (COI F and COI R) designed in the laboratory. The amplification yielded a specific fragment of approximately 550 base pairs, which was sequenced for further analysis. Sequence alignment revealed identity levels ranging from 82.8% to 99.7%, confirming the presence of A. fragariae. The resulting sequences were deposited in GenBank under the accession numbers LC804455 (A. fragariae isolate RB) and LC804456 (A. fragariae isolate LB), providing a valuable resource for future studies on this nematode species.